Recent and Advanced Trends in Cancer Treatments - Chithra RA; Mohamed Osman Elamin; Sucheta Karande (Medsci Publications, 2024)
Background: Cancer treatment remains a critical area of clinical research, with numerous approaches developed depending on tumor type and stage. Recent advances in genetic and immunotherapy, bioinformatics, and genetic science have revolutionized cancer diagnosis and treatment. Emerging technologies such as gene delivery, oncolytic virotherapy, suicide gene therapy, and CRISPR/Cas9 offer promising therapeutic avenues. Methods: This review provides a detailed analysis of the latest techniques of Gene therapy, artificial intelligence, Nanocarrier Delivery Systems, Immunotherapy, CAR T-Cell Therapy, Epigenetics, Vaccines, and Clinical translation and assessing their therapeutic potential in cancer treatment. A review of early critical studies focused on the integration of immunotherapy, nanotechnology, and artificial intelligence (AI) in cancer therapies with emphasis on targeted delivery systems and precision medicine. Results: The review highlights the synergistic effects of combining targeted therapies with immunotherapy, particularly immune checkpoint inhibitors and CAR-T cell therapy. Therapies such as CRISPR/Cas9 demonstrate significant potential in cancer targeting, while advancements in nanocarrier delivery systems offer enhanced precision with reduced side effects. AI's role in improving cancer diagnosis and personalized treatment is also underscored. Conclusion: This comprehensive analysis of recent therapeutic approaches and technological advancements addresses gaps in previous reviews and offers updated insights into cutting-edge cancer treatments. The review emphasizes the evolving role of immunotherapy, nanotechnology, AI, and nanotechnology, providing clinicians and researchers with the most current and relevant information for optimizing cancer treatment strategies.